Large Infrastructure Projects in Germany Between Ambition and Realities - Kostka, Genia; Fiedler, Jobst; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
This book presents an analysis of why some large infrastructure projects are delayed or compromised and offers important insights into the better delivery of future projects. It provides an important reaction to the ambitious €315 billion investment plan devised by the European Commission, wherein Europe's infrastructure is a key investment target. Germany is adopted as a focus, as Europe's largest economy, and a nation that has seen significant delays and tensions in the delivery of key infrastructure projects. The contributions to this volume demonstrate various patterns for infrastructure assets and illustrate how factors such as poor project governance, early planning mistakes, inappropriate risk management and unforeseen technological challenges influence delivery. The in-depth case studies on the Berlin Brandenburg Airport, the Hamburg Elbphilharmonie, and offshore wind parks show how project delivery can face massive problems, and illuminating solutions are offered to these problems. Overall, the case of Germany also offers the opportunity to assess various new forms of project delivery, such as public-private partnerships (PPP), and the risks and opportunities of ambitious first-mover 'pioneer' projects. The book will be of great interest for scholars and upper-level students of human geography, business and management, as well as policy makers.
Chapter 1. Introduction; Genia Kostka and Jobst Fiedler -- Chapter 2. Large Infrastructure Projects in Germany: A Cross-sectoral Analysis; Genia Kostka and Niklas Anzinger -- Chapter 3. The Elbphilharmonie Hamburg; Jobst Fiedler and Sascha Schuster -- Chapter 4. Berlin Brandenburg Airport; Jobst Fiedler -- Chapter 5. Offshore Wind Power Expansion in Germany: Scale, Patterns and Causes of Time Delays and Cost Overruns; Genia Kostka and Niklas Anzinger -- Chapter 6. Conclusion; Jobst Fiedler, Genia Kostka, Niklas Anzinger and Sascha Schuster.
Keywords: Social sciences; Sociology, Urban; Social Sciences; Urban Studies/Sociology.; Electronic books